EVOLUTION OF WIRELESS (CELLULAR) COMMUNICATION NETWORKS - L. F. Chernogor; M. B. Shevelev (Radio Physics and Radio Astronomy)
Subject and Purpose. One of today’s challenges in contemporary radio physics is exploring the terahertz frequency range which holds immense promise for revolutionary new applications in part at the level of wireless communication systems. A substantial frequency capacity of the range theoretically permits a usable frequency band expansion to a hundred terahertz. The data transfer rate can increase by many orders of magnitude, surpassing the capabilities of current networks. An urgent research priority involves assessing the potential growth rates of wireless communication network resources. The immediate purpose of this paper is to suggest simple mathematical models developed to predict the growth rates of wireless (cellular) communication network resources over the next 20 to 25 years.